Host species of a sexual-parasite do not differentiate between clones of Amazon mollies. (28th December 2017) - Makowicz, Amber M; Muthurajah, Darrshini S; Schlupp, Ingo
Abstract : Species recognition is an important process prior to copulation that is thought to be continuous with mate and individual recognition. Amazon mollies—a sperm-parasitic fish—show recognition at the clonal level; here, we investigate if the sexual host species have the same capabilities. We show that both sexual hosts do not exhibit a detectable preference for different clonal females. This raises the possibility that clonal recognition evolved in the Amazon molly, not in its ancestors. Abstract: A major mechanism of prezygotic isolation is the ability for individuals to recognize conspecifics. In gynogenetic species complexes, the sexual host species occur in syntopy with the unisexual species that relies on the sexuals' sperm for reproduction, which provide an excellent opportunity for the evolution of fine-tuned species recognition capabilities. Here, we examined if males and females from both parental species (sailfin molly, Poecilia latipinna, and Atlantic molly, P. mexicana ) can distinguish between different clonal lineages of the hybrid, all-female Amazon molly ( P. formosa ). Both males and females were presented with the choice of 2 different pairings of Amazon mollies: 1) a sympatric female and an allopatric female; and 2) 2 sympatric females. We found that neither males nor females of sailfin or Atlantic mollies show a preference for a clone type. These results suggest that either the parental species do not have the ability to recognize different Amazon molly clones or they recognize but do not have a preference for a specific Amazon molly clone.